PENGARUH WAKTU PEMBERIAN PUPUK KANDANG TERHADAP PERTUMBUHAN VEGETATIF TABULAMPOT JAMBU AIR MDH (Syzygium samarangense (Blume) Merr. & L.M. Perry) - Yusfi Afidah; Fatimatuz Zuhro; Hasni Ummul Hasanah; Sugeng Winarso; Mohammad Hoesain (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
MDH water apple is one type of fruit plant that can be cultivated intabulampot. Facts in the field indicate that planting it in tabulampotmakes the plant bear fruit faster. Another factor that determines theproduction of MDH guava is fertilization, including fertilizing withorganic matter. Besides giving organic fertilizer, the right time whenapplying fertilizer is also important in determining the growth of MDHguava. The purpose of this study was to determine the effect of the timeof manure on the vegetative growth of MDH guava. This research wasconducted in the green house in March to August 2018. This study useda randomized block design with 9 repetitions and 3 treatments, namely:(1) fertilization at the beginning of planting, (2) fertilization in the 1stand 3rd month after planting, and (3) fertilization in the 1st and 5thmonths after planting. Data were analyzed using ANOVA test. Theresults of this study indicate that manure has a significant effect on thenumber of leaf parameters, but does not significantly affect plantheight, number of primary branches, and number of secondarybranches. The best growth results were obtained at two time offertilizing in MDH water apple. Keyword : MDH water apple, manure, tabulampot, time of fertilizing.